Parallel-excision infrabrow blepharoplasty with extensive excision of the orbicularis oculi muscle in an Asian population - Yoon Jae Lee; SeongAe Kim; Jisung Lee; Joong Geel Chung; Young Joon Jun (Archives of Plastic Surgery, 2020)
Background Infrabrow blepharoplasty has become a common surgical method used to rejuvenate aged upper eyelids in Asians. In this paper, we describe the parallel excision method for infrabrow blepharoplasty as a useful alternative to the conventional elliptical excision method. The authors’ experience over a 3-year period is presented and reviewed. Methods A retrospective review of parallel excision infrabrow blepharoplasty cases at our hospital between 2014 and 2017 was performed. Three oculoplastic surgeons compared preoperative and postoperative photographs using the Strasser grading system. Results From the medical records of 123 patients, a total of 93 patients with moderate-to-severe bilateral dermatochalasis were selected as subjects. The exclusion criterion was levator function less than 8 mm. The total mean follow-up period was 2 years (range, 0.5–3.5 years). The mean skin excision height and width were 9.75 mm (range, 5–16 mm) and 58.51 mm (range, 42–75 mm), respectively. All patients who underwent surgery recovered without major complications, and all patients had high levels of satisfaction and improvements in their visual field. In the Strasser evaluation performed by the oculoplastic surgeons, most patients were found to have excellent results. Conclusions The parallel excision method for infrabrow blepharoplasty is a safe and effective technique that yields more natural- and youthful-looking eyelids than the conventional elliptical excision method. In our method, more effective manipulation of the orbicularis oculi muscle led to a reduction in frontalis compensation, resolution of sunken eyelids, and correction of lateral hooding.